Industrial Symbiosis - Recommendations on a business framework conducive for successful Industrial Symbiosis at the Kwinana industrial area - Oughton Chris; Kurup Biji; Anda Martin; Ho Goen (Renewable Energy and Environmental Sustainability, 2023)
With an extensive presence in the world of Industrial Symbiosis literature, the Kwinana industrial area in Perth, Western Australia is a powerhouse of integrated heavy industrial activity. From when its first entrant arrived in 1955, development has been strong, and now it presents a complex industrial cluster with a wide range of industrial enterprises present, ranging from several major industrial multi-product manufacturers to those filling niche markets. Formal reporting of its economic contribution has occurred periodically over 40 yr, with one of the features of this being a series of four earlier iterations, and in this paper, the fifth, of a schematic diagram that identifies the enterprises engaged in symbiotic relationships and the nature of the associated materials exchanged. While the earlier reports concentrated solely on the traditional materials exchanges, the present study (data collected in 2021) went beyond these to gather additional data on what the authors are proposing as additional dimensions of the traditional Industrial Symbiosis framework. Aspects of Kwinana's skilled workforce, its support industry base, and its overlying governance framework were studied to provide insights into what role they play in explaining why some industrial clusters appear to provide a supportive business environment, and why other clusters struggle to gain momentum. The new study identified that the novel posited dimensions of Industrial Symbiosis are interlinked at the precinct level, and that at the macro (societal) level, they combine to contribute to the effectiveness of the Circular Economy.